DISCOURSE ANALYSIS OF OPRAH WINFREY'S SPEECH AT 2024 DEMOCRATIC NATIONAL CONVENTION - Saleh, Kawther Adnan; Abed, Hind Mohammed; Fattah, Sahar Abdul-Razzaq (PT. Antis International Publisher, 2026)
Objective: This study elucidates Oprah Winfrey's address at the 2024 Democratic National Convention. It seeks to examine the many forms of lexical and grammatical coherence according to the theory of Halliday and Hasan (1976). Method: The data analysis indicated that the use of both lexical and grammatical cohesion significantly contributes to the development of cohesive, clear, and comprehensible speech. Results: The research indicated that